The Influence of Customer Relationship Management and Brand Image on Customer Loyalty through Satisfaction - Zuhri, M Ali Tsabit; Palupiningdyah, Palupiningdyah (Management Analysis Journal, 2018)
The purpose of this study was to determine the direct and indirect effects of customer relationship management and brand image on customer loyalty through satisfaction in the official Suzuki Indosun Semarang workshop. The population in this study were consumers of the Semarang Indosun Suzuki official workshop who had served more than once with a total sample of 115 respondents, through non-probability sampling techniques, namely accidental sampling. Data collection was obtained through questionnaires. Data analysis method in this study consisted of validity, reliability, classical assumption test, hypothesis test, and path analysis. Instrument testing is carried out using the IBM SPSS Statistics 23.0 program. The results show that customer relationship management and brand image have a significant effect on satisfaction. Customer relationship management and brand image have a significant effect on customer loyalty. Satisfaction has a significant effect on customer loyalty. The results of the path analysis test show that customer relationship management and brand image have a significant effect on customer loyalty through satisfaction. So that it can be said that satisfaction is able to become an intervening variable the influence of customer relationship management and brand image on customer loyalty.